J1110+4817 – a compact symmetric object candidate revisited. Issue 2 (12th June 2020) - Krezinger, Máté; Frey, Sándor; An, Tao; Jaiswal, Sumit; Zhang, Yingkang
ABSTRACT: Compact symmetric objects (CSOs) are radio-emitting active galactic nuclei (AGNs) typically with a double-lobed radio structure confined to within 1 kpc. CSOs represent the earliest evolutionary phase of jetted AGNs. Some of them may eventually evolve into large-scale extended double sources, while others stall within the host galaxy and die out, depending on the longevity of nuclear activity, the jet power, and parameters of the surrounding galactic environment. Studying CSOs is a useful tool for understanding the evolution of the galaxies and the interactions between the jets and the medium of the host galaxy. Based on milliarcsec-resolution imaging observations using very long baseline interferometry (VLBI), it is not always straightforward to distinguish between a compact double-lobed or a core–jet structure. The quasar J1110+4817 was considered a CSO candidate in the literature earlier, but because of the lack of clear evidence, it could not be securely classified as a CSO. Here we present a comprehensive analysis of archival multifrequency VLBI observations combined with accurate Gaia optical astrometric information. Lower frequency VLBI images reveal an extended radio feature nearly perpendicular to the main structural axis of the source, apparently emanating from the brighter northern feature, which is rare among the known CSOs. While the presence of a binary AGN system cannot be fully excluded, the most plausible explanation is that J1110+4817 is a CSO.